Uma batalha naval concentra por si só um século de glórias: Riachuelo na história e na memória - José Miguel Arias Neto (Navigator)
This article aims to develop a reflection on the representations, memory and appropriations of the Battle of Riachuelo by various political groups and military throughout the Second Empire and the first two Republican decades. It has as object/sources the press in general, the military press, diaries, memoirs, essays, brochures and images. The goal is to understand the multiple meanings that the Brazilian victory in Riachuelo has acquired throughout history and reflect on its possible contemporary meanings.